Trash2move as a community-based development model for sustainable plastic waste management - Nisaul Khairiyah (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Plastic waste management into products with economic value is one of the efforts that demostrates a positive interaction between humans and the environment. This program encourages community participation as a form of community empowerment, while also contributing to reducing pollution and creating sustainable impacts on the environment and socio-economy. Trash2Move is a community of Generation Z in Padang City founded in 2022 that processes plastic waste into products of economic value. The program run by Trash2Move implements a community-based circular economy scheme, where community-provided plastic waste can be exchanged for necessities as a direct benefit. Trash2Move then processes the plastic waste into products of economic value that will be marketed again. Methods: Data was obtained through interviews with the founders of Trash2Move and a review of supporting documents. Findings: The results of this study show that Trash2Move, a plastic waste management community initiated by Generation Z, has successfully implemented a community-based circular economy model for waste management. The program of exchanging waste for necessities, recycled product innovations, and digital education campaigns has increased community participation and environmental awareness. Incentives have triggered behavioral change, while Generation Z’s digital literacy has expanded the reach of education. Trash2Move contributes to achieving SDG 12, despite still facing limitations in support and a lack of quantitative impact measurement. Conclusion: This study recommends further research using quantitative and comparative approaches to deepen understanding of the effectiveness of community-based waste management models led by the younger generation. Novelty/Originality of this article: This study analyzes the role of Trash2Move in plastic waste management in Padang City, particularly its contribution to increasing community participation and environmental awareness. The research also examines how Generation Z leadership, through a circular economy approach, shapes a community development model that supports achieving SDG 12 on sustainable consumption and production.